A disaggregated analysis of the environmental Kuznets curve for industrial CO2 emissions in China. (15th March 2017) - Wang, Yuan; Zhang, Chen; Lu, Aitong; Li, Li; He, Yanmin; ToJo, Junji; Zhu, Xiaodong
Highlights: The existence of EKC hypothesis for industrial carbon emissions is tested for China. A semi-parametric panel regression is used along with the STIRPAT model. The validity of the EKC hypothesis varies across industry sectors. The EKC relation to income exists in the electricity and heat production sector. The EKC relation to urbanization exists in the manufacturing sector. Abstract: The present study concentrates on a Chinese context and attempts to explicitly examine the impacts of economic growth and urbanization on various industrial carbon emissions through investigation of the existence of an environmental Kuznets curve. Within the Stochastic Impacts by Regression on Population, Affluence and Technology framework, this is the first attempt to simultaneously explore the income/urbanization and disaggregated industrial carbon dioxide emissions nexus, using panel data together with semi-parametric panel fixed effects regression. Our dataset is referred to a provincial panel of China spanning the period 2000–2013. With this information, we find evidence in support of an inverted U-shaped curve relationship between economic growth and carbon dioxide emissions in the electricity and heat production sector, but a similar inference only for urbanization and those emissions in the manufacturing sector. The heterogeneity in the EKC relationship across industry sectors implies that there is urgent need to design more specific policies related to carbon emissions reduction for various industry sectors. Also, these findings contribute to advancing the emerging literature on the development-pollution nexus.